2018
DOI: 10.1089/gtmb.2018.0110
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Complement FactorC2/C3/CFB/CFHPolymorphisms and Age-Related Macular Degeneration: A Meta-Analysis

Abstract: Our findings from this analysis confirmed the protective role of C2/CFB/CFH polymorphisms in the development of AMD, but showed that the single nucleotide polymorphism in C3 was a high-risk factor for AMD. The racial analysis results suggested that the effect of variant alleles was stronger in Caucasians than Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 78 publications
4
26
0
Order By: Relevance
“…Eculizumab is an effective terminal pathway blocker; however, for several years its use has been restricted to only two ultra‐rare diseases, PNH and aHUS, and latterly approved for MG treatment. In recent years, pathological roles of complement in more common conditions like MG, age‐related macular degeneration and neurodegeneration have been demonstrated, building a case for the broader use of anti‐complement drugs in the clinic . Cost and convenience are limiting factors in broadening anti‐complement drug use; current cost and dosing schedules for Eculizumab are incompatible with use in the treatment of common, chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Eculizumab is an effective terminal pathway blocker; however, for several years its use has been restricted to only two ultra‐rare diseases, PNH and aHUS, and latterly approved for MG treatment. In recent years, pathological roles of complement in more common conditions like MG, age‐related macular degeneration and neurodegeneration have been demonstrated, building a case for the broader use of anti‐complement drugs in the clinic . Cost and convenience are limiting factors in broadening anti‐complement drug use; current cost and dosing schedules for Eculizumab are incompatible with use in the treatment of common, chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al performed a systematic analysis and suggested rs641153 in the CFB gene was a protective factor in advanced AMD both in Caucasians and Asians [17]. Rs547154 and rs9332739 SNPs had both decreased correlations to AMD risk [15]. In a word, we should deep explore these partners of CFI gene, and gene-gene interactions in the development of AMD in the next step.…”
Section: Discussionmentioning
confidence: 99%
“…A dysfunctional complement pathway has been proposed to increase retinal cell damage via increased formation of drusen deposits, atrophy, and cell degeneration and progression to choroidal neovascularization (CNV) [13,14]. So far, component 2 (rs547154 and rs9332739) [15], component 5 [16], factor B (L9H) [17] and factor H (Y402H) [18] polymorphisms have been observed associated with AMD susceptibility. In 2015, our team first reported the association between component 3 gene polymorphisms and AMD risk…”
Section: Introductionmentioning
confidence: 99%
“…A genome-wide association study (GWAS) showed a clearer view about significant links between AMD risk and genetic variations in 2005, suggesting AMD is a polygenic disease [10], which triggered numerous studies involving the genetic associations of AMD in the following 15 years [11][12][13]. So far, AMRS2 rs10490924 polymorphism, SNPs from complement factor H, C2/CFB, complement component C3, APOE haplotypes have been confirmed as being associated with susceptibility of AMD [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%